Lemna paucicostata Hegelm. 6746: DEVELOPMENT OF STANDARDIZED GROWTH CONDITIONS SUITABLE FOR BIOCHEMICAL EXPERIMENTATION - Datko, Anne H. (1980)
Photoautotrophic and mixotrophic growth of Lemna paucicostata Hegelm. 6746 (formerly Lemna perpusilla Torr. 6746) was investigated to establish standardized conditions for biochemical studies. Optimal temperature for growth was 29 to 30 C. The medium used previously (Datko AH, Mudd SH, Giovanelli J 1977 J Biol Chem 252: 3436-3445) was modified by inclusion of NH(4)Cl, decreasing macronutrient and ethylenediamine tetraacetate concentration, increasing micronutrient concentration, and inclusion of bicarbonate (for photoautotrophic growth) or 2-(N-morpholino)ethanesulfonic acid (for mixotrophic growth) buffers. Varying the sulfate concentration between 14 and 1 millimolar had no effect on growth. For photoautotrophic growth in the new medium (medium 4), the effects of CO(2) concentration, light intensity, and pH were measured. Under the optimal conditions, a multiplication rate (MR) of 300 to 315, equivalent to a doubling time of 23 to 24 hours was obtained. Addition of glutamine or asparagine did not increase this MR. For mixotrophic growth in low light, the effects of sucrose concentration and pH were determined. Under optimal conditions, MR was 210. A concentration of sucrose less than maximal for growth was chosen for the medium for experiments which will include (14)C-labeling of intermediates. MR under these conditions was 184. Growth was equally good in medium 4 and in half-strength Hutner's medium when sulfate was high (0.4 to 1 millimolar), but better in medium 4 when sulfate was low (20 micromolar). Growth rates could be restored to normal in half-strength Hutner's with low sulfate by decreasing the molybdate concentration. By modifying medium 4 to contain very low amounts of sulfate, and by preconditioning medium and plants, it was shown that there was an increment in plant protein of approximately 2.5 micrograms per nanomole of added MgSO(4). Colonies undergoing sulfur limitation exhibited a slow growth rate and a high frond to colony ratio. Molybdate and selenate produced growth inhibition reversible by sulfate. Conditions were developed in which the plants could be maintained indefinitely in the presence of either molybdate or selenate in altered metabolic steady-states with lowered growth rates and protein per frond.